Students' Perception of the Role of Collaborative Learning in Promoting Language Mediation Skill in Translation Course - Kuswandari, Dwi Septi; Setyaningrahayu, Indri Retno (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2025)
Collaborative learning has been applied in language learning. One part of language teaching is translation, a language mediation skill involving transfer of meaning from one language to another. Past literature has revealed that although collaborative learning gives many advantages to students in the translation class, there is still limited research discussing the potential effects of collaborative learning on students' translation skills as language mediation. This study aims to fill this gap by investigating the students' perception of collaborative learning's potential effects in enhancing language mediation skills. A questionnaire consisting of some close-ended and open-ended questions was distributed to 62 participants who were fourth-year students of the English Education Program at Universitas Kristen Satya Wacana, Indonesia. The data analysis indicated that students gave moderately to highly positive responses on the impacts of collaborative learning on their translation. The research overall revealed that collaborative learning had considerable impacts on students' translation competence, especially in extra-linguistic, strategic, and bilingual competence.